Carbon dioxide removal for methane upgrade by a VSA process using an improved 13X zeolite - Marta C. Campo (2016)
The main polluting compound in natural gas is CO2. Therefore, the removal of CO2 from that fuel is a major process in the industry for upgrading its energy content. The separation by Pressure Swing Adsorption can be efficient energy wise and many microporous zeolites have been mentioned in the literature as promising adsorbents to carry out this separation. In this work, adsorption equilibrium isotherms of methane, nitrogen and carbon dioxide on an improved 13X zeolite were measured at three temperatures (308, 323 and 348 K) up to 5 bar. The adsorption capacity of carbon dioxide at 323 K and 5 bar was approximately 50% higher than values reported in literature. The experimental adsorption equilibrium isotherms of nitrogen and methane were well described by the Langmuir equation, while carbon dioxide isotherms were fitted with Toth equation. Single and ternary breakthrough curves were measured and simulated with a mathematical model for fixed bed adsorbers. A pilot scale 4-step Vacuum Swing Adsorption cycle was suggested and validated experimentally to remove carbon dioxide down to 3.7% in the methane stream. An industrial scale process was designed in order to produce an upgraded methane stream with less than 2% carbon dioxide. A methane recovery of 96% and a power consumption of 4.27 Wh/mol(CH4) were obtained.